2014
DOI: 10.1007/s00018-014-1635-y
|View full text |Cite
|
Sign up to set email alerts
|

Fructose transport-deficient Staphylococcus aureus reveals important role of epithelial glucose transporters in limiting sugar-driven bacterial growth in airway surface liquid

Abstract: Hyperglycaemia as a result of diabetes mellitus or acute illness is associated with increased susceptibility to respiratory infection with Staphylococcus aureus. Hyperglycaemia increases the concentration of glucose in airway surface liquid (ASL) and promotes the growth of S. aureus in vitro and in vivo. Whether elevation of other sugars in the blood, such as fructose, also results in increased concentrations in ASL is unknown and whether sugars in ASL are directly utilised by S. aureus for growth has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…In agreement with our findings, previous studies demonstrated that a high risk of S. aureus respiratory infection is correlated with an increased glucose concentration in blood and airway spaces (41). Another recent study demonstrated that S. aureus, upon internalization in A549 cells, highly increased transcription of transporters of inorganic ions, nucleotides, and carbohydrates, including UhpT (42).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, previous studies demonstrated that a high risk of S. aureus respiratory infection is correlated with an increased glucose concentration in blood and airway spaces (41). Another recent study demonstrated that S. aureus, upon internalization in A549 cells, highly increased transcription of transporters of inorganic ions, nucleotides, and carbohydrates, including UhpT (42).…”
Section: Discussionsupporting
confidence: 92%
“…Airway epithelial monolayers maintained their transepithelial resistance when glucose in the basolateral chamber was replaced with fructose, as previously reported [22]. As fructose did not bind to GBP–BADAN, ASL from cells grown in basolateral fructose was used to obtain ASL in which glucose was not present and correct for background fluorescence.…”
Section: Resultsmentioning
confidence: 80%
“…We propose that dapagliflozin exerts its anti‐infective effect by restricting glucose availability for P. aeruginosa growth/survival in the lung through a reduction in blood and ASL glucose concentrations. In support of this, genetic impairment of sugar transport pathways in P. aeruginosa and S. aureus that limited sugar uptake had a similar effect on bacterial growth/survival in the lung to that of dapagliflozin (Pezzulo et al, ; Garnett et al, ; Gill et al, ). Reduction of airway glucose in the distal mouse lung by manipulation of glucose transport pathways also reduced bacterial load (Oliveira et al, ).…”
Section: Discussionmentioning
confidence: 87%